Surface-modified liquid metal microcapsule and preparation method thereof, resin material and preparation method thereof, liquid metal microcapsule reinforced fiber fabric self-lubricating composite material and preparation method thereof
By using surface-modified liquid metal microcapsules in fiber fabric self-lubricating composite materials, the problem of insufficient thermal conductivity and tribological properties of composite materials under high-speed operating conditions is solved, and performance improvement and service life are achieved.
Patent Information
- Application Number
- CN202411824861.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
Under high-speed use conditions, friction heat accumulation can easily lead to wear and failure of polymer composite materials. How to improve the thermal conductivity and tribological properties of self-lubricating composite materials of fiber fabrics is a technical problem that needs to be solved urgently.
The thermal conductivity and tribological properties of the composite material are improved by preparing surface-modified liquid metal microcapsules, including liquid metal and organic polymer shells that encapsulate them, and growing two-dimensional layered materials in situ on the outer surface of the shell.
It significantly improves the thermal conductivity of the self-lubricating composite material of liquid metal microcapsule reinforced fiber fabrics and the tribological properties under high-speed operating conditions, and extends the service life of the lubricating metal parts.
Smart Images

Figure CN119634721A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of composite materials and the technical field of lubricating materials, and specifically relates to surface-modified liquid metal microcapsules and a preparation method thereof, resin materials and a preparation method thereof, and liquid metal microcapsule-reinforced fiber fabric self-lubricating composite materials and a preparation method thereof. Background Art
[0002] Self-lubricating spherical plain bearings are composed of outer bearing rings, inner rings and fiber fabric self-lubricating padding materials between the inner and outer rings. They have the advantages of high load-bearing capacity, low friction, wear resistance, long life, and maintenance-free. They are widely used in key and important parts such as aircraft transmission systems, control systems, and power systems, and have a vital impact on aircraft flight safety. Due to the advantages of fiber fabric self-lubricating padding materials such as high load-bearing capacity, wear resistance, strong designability, and good dimensional stability, they are widely used in a large number of moving parts such as landing gear, flaperons, rotor systems, and aircraft engines of domestic and foreign aircraft models, and have very good application prospects.
[0003] At present, fiber fabric self-lubricating pad materials are usually composed of polymer composite materials. When self-lubricating spherical plain bearings are used at high speed, the accumulated friction heat easily leads to wear and failure of polymer composite materials. Therefore, how to improve the thermal conductivity and tribological properties of fiber fabric self-lubricating composite materials under high-speed use conditions is a technical problem that needs to be solved to improve the performance of self-lubricating spherical plain bearings. Summary of the invention
[0004] The purpose of the present invention is to provide a surface-modified liquid metal microcapsule and a preparation method thereof, a resin material and a preparation method thereof, a liquid metal microcapsule reinforced fiber fabric self-lubricating composite material and a preparation method thereof. The surface-modified liquid metal microcapsule provided by the present invention has excellent lubrication and thermal conductivity. The liquid metal microcapsule reinforced fiber fabric self-lubricating composite material obtained thereby has improved thermal conductivity and excellent tribological properties under high-speed conditions, and the service life of metal parts as a lubricating layer is significantly improved.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a surface-modified liquid metal microcapsule, comprising a liquid metal microcapsule and a two-dimensional layered material in-situ grown on the outer surface of the liquid metal microcapsule; the liquid metal microcapsule comprises liquid metal and an organic polymer shell layer wrapping the liquid metal, the liquid metal is of micro-nano-scale particle size, and the organic polymer shell layer comprises polydopamine or a polydopamine copolymer.
[0007] Preferably, the liquid metal includes gallium-based liquid metal and / or lithium-based liquid metal;
[0008] The polydopamine copolymer includes a copolymer of tannic acid and / or polyethyleneimine and dopamine;
[0009] The two-dimensional layered material includes one or more of molybdenum disulfide, tungsten disulfide and layered MOF materials.
[0010] The present invention provides a method for preparing the surface-modified liquid metal microcapsules described in the above technical solution, comprising the following steps:
[0011] The liquid metal is sheared and dispersed to obtain a micro-nano-scale liquid metal dispersion;
[0012] The micro-nanoscale liquid metal dispersion is coated with an organic coating material through a polymerization reaction to obtain liquid metal microcapsules, wherein the organic coating material includes dopamine;
[0013] The surface of the liquid metal microcapsule is modified by solvent thermal reaction using raw materials for preparing the two-dimensional layered material, and the two-dimensional layered material is in situ grown on the surface of the liquid metal microcapsule to obtain the surface-modified liquid metal microcapsule.
[0014] Preferably, the shearing speed of the shear dispersion is 1000 to 200000 r / min.
[0015] The present invention provides a resin material, comprising a thermosetting resin solution and a lubricating filler uniformly dispersed in the thermosetting resin solution, wherein the lubricating filler is the surface-modified liquid metal microcapsule described in the above technical solution or the surface-modified liquid metal microcapsule prepared by the preparation method described in the above technical solution.
[0016] Preferably, the thermosetting resin solution includes one or more of a polyureaimide resin solution, a polyimide resin solution, an epoxy resin solution and a phenolic resin solution;
[0017] The mass of the lubricating material accounts for 0.01-6% of the mass of the thermosetting resin solution.
[0018] The present invention provides a method for preparing the resin material described in the above technical solution, comprising the following steps:
[0019] The resin material is prepared by an in-situ polymerization method using a thermosetting resin polymerization precursor and a lubricating filler.
[0020] The present invention provides a liquid metal microcapsule reinforced fiber fabric self-lubricating composite material, comprising a resin matrix and fiber fabric distributed in the resin matrix, wherein the resin matrix is formed by the resin material described in the above technical solution or a resin material prepared by the preparation method described in the above technical solution.
[0021] Preferably, the mass of the fiber fabric accounts for 30-85% of the total mass of the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material.
[0022] The present invention provides a method for preparing the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material described in the above technical solution, comprising the following steps:
[0023] The fiber fabric grey cloth and the resin material are compounded to obtain the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material; the compounding includes repeated impregnation-drying operations.
[0024] The present invention provides a surface-modified liquid metal microcapsule, comprising a liquid metal microcapsule and a two-dimensional layered material in-situ grown on the outer surface of the liquid metal microcapsule; the liquid metal microcapsule comprises a liquid metal and an organic polymer shell layer encapsulating the liquid metal, the liquid metal is a micro-nano particle size, and the organic polymer shell layer comprises polydopamine or a polydopamine copolymer. The present invention encapsulates a liquid metal with excellent lubrication and thermal conductivity in an organic polymer shell layer, and simultaneously in-situ grows a two-dimensional layered material on the outer surface of the organic polymer shell layer, so that the surface-modified liquid metal microcapsule provided by the present invention can effectively improve the tribological performance of the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material under high-speed working conditions.
[0025] The present invention provides a method for preparing surface-modified liquid metal microcapsules as described in the above technical solution, comprising the following steps: shearing and dispersing liquid metal to obtain a micro-nanoscale liquid metal dispersion; coating the micro-nanoscale liquid metal dispersion with an organic coating material through a polymerization reaction to obtain liquid metal microcapsules, wherein the organic coating material includes dopamine; surface-modifying the liquid metal microcapsules with a solvent-thermal reaction using a raw material for preparing a two-dimensional layered material, and in-situ growing a two-dimensional layered material on the surface of the liquid metal microcapsules to obtain surface-modified liquid metal microcapsules. The present invention successfully synthesizes liquid metal microcapsules by combining mechanical dispersion with interfacial polymerization, and the obtained liquid metal microcapsules have a small particle size and are evenly distributed; finally, in-situ growing a two-dimensional layered material on the surface of the liquid metal microcapsules through a solvent-thermal reaction can ensure that the two-dimensional layered material is evenly distributed on the outer surface of the organic polymer shell layer, and the outer surface of the liquid metal microcapsules is modified, thereby further improving the lubrication performance of the liquid metal microcapsules.
[0026] The present invention provides a resin material, including a thermosetting resin solution and a lubricating filler uniformly dispersed in the thermosetting resin solution, wherein the lubricating filler is the surface-modified liquid metal microcapsule described in the above technical solution or the surface-modified liquid metal microcapsule prepared by the preparation method described in the above technical solution. The present invention uses the surface-modified liquid metal microcapsule as a lubricating filler to modify the thermosetting resin solution, and the obtained resin material forms a resin matrix. When preparing a fiber fabric self-lubricating composite material, it can achieve the improvement of the thermal conductivity of the composite material and the improvement of the tribological performance of the composite material under high-speed conditions, and finally achieve the technical effect of improving the service life of metal parts using the fiber fabric self-lubricating composite material as a lubricating layer.
[0027] The present invention provides a method for preparing the resin material described in the above technical solution, comprising the following steps: preparing the resin material by in-situ polymerization using a thermosetting resin polymer precursor and a lubricating filler. The present invention uses a thermosetting resin polymer precursor and a lubricating filler for in-situ polymerization, and the surface-modified liquid metal microcapsules and the thermosetting resin polymer precursor are subjected to polymerization reaction, and the thermosetting resin precursor and the surface-modified liquid metal microcapsules in the obtained resin material are connected by chemical bonds, thereby effectively improving the dispersion stability and uniformity of the surface-modified liquid metal microcapsules in the resin matrix, thereby achieving the improvement of the thermal conductivity of the composite material and the improvement of the tribological properties of the composite material under high-speed conditions, and finally achieving the technical effect of improving the service life of metal parts using the fiber fabric self-lubricating composite material as a lubricating layer.
[0028] The present invention provides a liquid metal microcapsule reinforced fiber fabric self-lubricating composite material, comprising a resin matrix and a fiber fabric distributed in the resin matrix, wherein the resin matrix is formed by the resin material described in the above technical solution or the resin material prepared by the preparation method described in the above technical solution. The liquid metal microcapsule reinforced fiber fabric self-lubricating composite material provided by the present invention has improved thermal conductivity and excellent tribological performance under high-speed working conditions, and the service life of metal parts as a lubricating layer is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The wear rate of the self-lubricating liner material prepared in Example 1 of the present invention and Comparative Examples 1 to 2;
[0030] Figure 2 The friction coefficient of the self-lubricating gasket material prepared in Example 1 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0031] The present invention provides a surface-modified liquid metal microcapsule, comprising a liquid metal microcapsule and a two-dimensional layered material in-situ grown on the outer surface of the liquid metal microcapsule; the liquid metal microcapsule comprises liquid metal and an organic polymer shell layer wrapping the liquid metal, the liquid metal is of micro-nano-scale particle size, and the organic polymer shell layer comprises polydopamine or a polydopamine copolymer.
[0032] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0033] The surface-modified liquid metal microcapsules provided by the present invention include liquid metal microcapsules. In the present invention, the liquid metal microcapsules include liquid metal and an organic polymer shell layer encapsulating the liquid metal, and the liquid metal has a micro-nano particle size. The liquid metal preferably includes gallium-based liquid metal and / or lithium-based liquid metal, and more preferably gallium-based liquid metal. In a specific embodiment of the present invention, the liquid metal is specifically Ga liquid metal. The particle size range of the liquid metal is 25nm to 3μm.
[0034] In the present invention, the polydopamine copolymer includes a copolymer of tannic acid and / or polyethyleneimine and dopamine. In the present invention, the organic polymer shell layer is specifically a copolymer of polydopamine, tannic acid and dopamine, or a copolymer of polyethyleneimine and dopamine.
[0035] The present invention encapsulates and stabilizes the liquid metal with micro-nano particle size through the organic polymer shell layer.
[0036] The surface-modified liquid metal microcapsules provided by the present invention include a two-dimensional layered material in situ grown on the outer surface of the liquid metal microcapsules. In the present invention, the two-dimensional layered material preferably includes one or more of molybdenum disulfide, tungsten disulfide and layered MOF materials, specifically molybdenum disulfide in the embodiment.
[0037] The present invention provides a method for preparing the surface-modified liquid metal microcapsules described in the above technical solution, comprising the following steps:
[0038] The liquid metal is sheared and dispersed to obtain a micro-nano-scale liquid metal dispersion;
[0039] The micro-nano-scale liquid metal dispersion is coated with an organic coating material through a polymerization reaction to obtain liquid metal microcapsules, wherein the organic coating material includes dopamine (denoted as PDA@LM in the present invention);
[0040] The surface of the liquid metal microcapsule is modified by solvent thermal reaction using raw materials for preparing two-dimensional layered materials, and two-dimensional layered materials are in situ grown on the surface of the liquid metal microcapsule to obtain surface-modified liquid metal microcapsule (denoted as MoS2@LM in the present invention).
[0041] The present invention shears and disperses the liquid metal to obtain a micro-nanoscale liquid metal dispersion. In the present invention, the shear dispersion reagent is preferably water, and in the embodiment, it is specifically deionized water. In the present invention, the shear dispersion preferably includes: mixing the liquid metal and water for shear dispersion, and the amount ratio of the liquid metal to the water is preferably (1-2) g: 100 mL. The shear dispersion is preferably completed in a shear dispersion device, and the shear speed of the shear dispersion is preferably 1000-200000 r / min, more preferably 2000-150000 r / min, and further preferably 5000-20000 r / min. The shear dispersion time is preferably 5-10 min.
[0042] After obtaining the micro-nano liquid metal dispersion, the present invention uses an organic coating material to coat the micro-nano liquid metal dispersion through a polymerization reaction to obtain liquid metal microcapsules, and the organic coating material includes dopamine. In the present invention, the coating preferably includes the following steps: shear mixing the micro-nano liquid metal dispersion and the organic coating material to obtain a mixed dispersion; mixing the mixed dispersion, water and tris buffer solution to perform a polymerization reaction to obtain the liquid metal microcapsules. The organic coating material includes dopamine, and dopamine is specifically dopamine hydrochloride. When the organic polymer shell layer is preferably a polydopamine copolymer, the polydopamine copolymer preferably includes a copolymer of tannic acid and / or polyethyleneimine and dopamine. The organic coating material preferably also includes tannic acid and / or polyethyleneimine. In the present invention, when the organic coating material further includes tannic acid and / or polyethyleneimine, the mass concentration of tannic acid in the mixed dispersion is preferably 0.05-0.1 g / mL; the mass concentration of polyethyleneimine in the mixed dispersion is preferably 0.05-0.1 g / mL. The mass ratio of the liquid metal to dopamine hydrochloride is preferably 2:1. The shear mixing time is preferably 25-30 min. The pH value of the tris buffer solution is preferably 8.5. The water used in the polymerization reaction is preferably deionized water, and the volume ratio of the water to the tris buffer solution is preferably 145:5-10. The polymerization reaction is preferably carried out under stirring, and the polymerization reaction time is preferably 36-48 h. After the polymerization reaction, a polymerization reaction liquid is obtained. The present invention preferably separates the polymerization reaction liquid into solid and liquid, and the obtained solid phase product is washed and dried in turn to obtain the liquid metal microcapsule. The solid-liquid separation is preferably suction filtration. The washing is preferably deionized water washing, and the number of washings is preferably 3-5 times. The drying is preferably drying, and the drying temperature is preferably 40°C.
[0043] After obtaining the liquid metal microcapsules, the present invention uses the raw materials for preparing the two-dimensional layered materials to perform surface modification on the liquid metal microcapsules through a solvent thermal reaction, and in situ grows the two-dimensional layered materials on the surface of the liquid metal microcapsules to obtain surface-modified liquid metal microcapsules. In the present invention, the two-dimensional layered material is specifically molybdenum disulfide, and the raw materials for preparing the molybdenum disulfide preferably include ammonium molybdate and thiourea, and the ammonium molybdate is specifically ammonium molybdate tetrahydrate. The solvent thermal reaction is preferably a hydrothermal reaction. The surface modification preferably includes the following steps: ultrasonically mixing the liquid metal microcapsules, water, ammonium molybdate and thiourea and then performing a hydrothermal reaction, the water is preferably deionized water, and the mass ratio of the liquid metal microcapsules and the ammonium molybdate is preferably 100:1200. The mass ratio of ammonium molybdate and thiourea is preferably 1200:1000. The present invention has no special requirements for the amount of water, and it is sufficient to ensure that the hydrothermal reaction proceeds smoothly. The hydrothermal reaction is preferably carried out in a hydrothermal reaction kettle, the temperature of the hydrothermal reaction is preferably 220°C, and the time is preferably 6 to 8 hours. After the hydrothermal reaction is completed, a hydrothermal reaction liquid is obtained. In the present invention, the solid phase product in the hydrothermal reaction liquid is preferably washed and dried in sequence to obtain the surface-modified liquid metal microcapsules. The washing is preferably deionized water washing, the number of washings is preferably 3 to 5 times, the drying is preferably oven drying, and the drying temperature is preferably 40°C.
[0044] The present invention provides a resin material, comprising a thermosetting resin solution and a lubricating filler uniformly dispersed in the thermosetting resin solution, wherein the lubricating filler is the surface-modified liquid metal microcapsule described in the above technical solution or the surface-modified liquid metal microcapsule prepared by the preparation method described in the above technical solution.
[0045] In the present invention, the thermosetting resin solution preferably includes one or more of a polyureaimide resin solution, a polyimide resin solution, an epoxy resin solution and a phenolic resin solution, and in the embodiment, it is a polyureaimide resin solution. The mass of the lubricating material accounts for 0.01-6% of the mass of the thermosetting resin solution, and in the embodiment, it can be 0.01%, 1%, 2%, 3%, 4%, 5% or 6%.
[0046] The present invention provides a method for preparing the resin material described in the above technical solution, comprising the following steps:
[0047] The resin material is prepared by an in-situ polymerization method using a thermosetting resin polymerization precursor and a lubricating filler.
[0048] In the present invention, when the thermosetting resin solution is specifically a polyureaimide resin solution, the thermosetting resin polymerization precursor preferably includes 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane (HFBAPP), 3,5-diaminobenzoic acid (DABA), hexamethylene diisocyanate and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA).
[0049] In the present invention, the in-situ polymerization preferably includes the following steps: dissolving HFBAPP and DABA in a first organic solvent to obtain a first mixed solution; in a protective gas atmosphere, dripping hexamethylene diisocyanate into the first mixed solution, stirring and mixing to obtain a second mixed solution; dissolving BTDA in a second organic solvent to obtain a BTDA solution; dripping the BTDA solution into the second mixed solution for a first-stage reaction to obtain a third mixed solution; mixing the third mixed solution with a lubricating filler for a second-stage reaction to obtain the resin material. In the present invention, the mass ratio of HFBAPP and DABA is preferably 4.1606:0.407. The mass ratio of HFBAPP and hexamethylene diisocyanate is preferably 4.1606:0.8999. The first organic solvent is preferably dimethylacetamide (DMAc). The present invention has no special requirements for the amount of the first organic solvent. The protective gas is preferably nitrogen, the stirring and mixing temperature is preferably 60°C, and the stirring and mixing time after the hexamethylene diisocyanate is added is preferably 8 to 10 hours. The second organic solvent is preferably dimethylacetamide (DMAc). The mass ratio of HFBAPP to BTDA is preferably 4.1606:1.7239. The speed of adding the BTDA solution is preferably 1 mL min -1 The time of the first stage reaction is preferably 1 to 2 hours. The time of the second stage reaction is preferably 11 to 12 hours. The temperature of the first stage reaction and the second stage reaction is preferably 60°C.
[0050] The present invention provides a liquid metal microcapsule reinforced fiber fabric self-lubricating composite material, comprising a resin matrix and fiber fabric distributed in the resin matrix, wherein the resin matrix is formed by the resin material described in the above technical solution or a resin material prepared by the preparation method described in the above technical solution.
[0051] The liquid metal microcapsule reinforced fiber fabric self-lubricating composite material provided by the present invention comprises a resin matrix, and the resin matrix is formed by the resin material described in the above technical solution or the resin material prepared by the preparation method described in the above technical solution. The resin matrix is formed by drying (removing the solvent) the resin material described in the above technical solution or the resin material prepared by the preparation method described in the above technical solution.
[0052] The liquid metal microcapsule reinforced fiber fabric self-lubricating composite material provided by the present invention comprises a fiber fabric distributed in the resin matrix. In the present invention, the fiber fabric is preferably woven from PTFE fibers and other reinforcing fibers. In a specific embodiment of the present invention, the fiber fabric is preferably woven from PEEK fibers and PTFE fibers (PEEK / PTFE).
[0053] In the present invention, the mass of the fiber fabric accounts for preferably 30-85% of the total mass of the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material, and more preferably 70-80%.
[0054] The present invention provides a method for preparing the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material described in the above technical solution, comprising the following steps:
[0055] The fiber fabric grey cloth and the resin material are compounded to obtain the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material; the compounding includes repeated impregnation-drying operations.
[0056] In the present invention, the drying is preferably drying. There is no special requirement for the repetition times of the "immersion-drying" to ensure that the mass percentage of the fiber fabric in the metal microcapsule reinforced fiber fabric self-lubricating composite material preferably meets 30-85%, more preferably 70-80%.
[0057] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0058] Comparative Example 1
[0059] (1) 4.1606 g (0.008025 mol) of HFBAPP and 0.4070 g of DABA were dissolved in 20 mL of DMAc under magnetic stirring. Subsequently, 0.8999 g (0.00535 mol, 1 equivalent) of hexamethylene diisocyanate was slowly added dropwise and stirred continuously for 8 h in a nitrogen atmosphere at 60 °C. Then, 1.7239 g (0.00535 mol, 1 equivalent) of BTDA was dissolved in 15 mL of DMAc and stirred at 1 mL min. -1 The mixture was added dropwise at a rate of 1.5 %. While keeping an ice bath, the reaction was continued for 11 hours to obtain a polyurea-amic acid solution.
[0060] (2) The PEEK / PTFE fiber fabric is repeatedly immersed and dried in a dilute solution of polyurea-amic acid until the mass fraction of the PEEK / PTFE fiber fabric in the fabric / resin composite material reaches 70-80wt%. Finally, the impregnated PEEK / PTFE self-lubricating fabric is bonded to the surface of the metal part and cured to obtain a PEEK / PTFE self-lubricating fabric composite material, and the mass fraction of the PEEK / PTFE fiber fabric in the fabric / resin composite material reaches 70-80wt%. Under the test conditions of a rotation speed of 600r / min and a load of 24.96MPa, the friction coefficient of the composite material is 0.082 and the wear rate is 6.82×10 -14 m 3 / N·m.
[0061] Comparative Example 2
[0062] (1) Add 1g of liquid metal (GaIn) into 100mL of deionized water, and use a high-speed shear dispersion device (shear speed between 8000r / min) to disperse the liquid metal into micro-nano particles (25nm~3μm). After 5min, add 0.5g of dopamine hydrochloride, wait for 25 minutes, and stop shearing and stirring. Add the above solution into 145mL of deionized water and stir to mix the solution evenly. Then drop 5mL of tris buffer solution (PH=8.5) and stir slowly for 48h to induce dopamine polymerization. Finally, collect the PDA@LM gray-black powder by filtration, wash it repeatedly with deionized water five times, and put it in a 40℃ oven to dry for 12h.
[0063] (2) 4.1606 g (0.008025 mol) of HFBAPP and 0.4070 g of DABA were dissolved in 20 mL of DMAc under magnetic stirring. Subsequently, 0.8999 g (0.00535 mol) of hexamethylene diisocyanate was slowly added dropwise and stirred continuously for 8 h in a nitrogen atmosphere at 60 °C. Then, 1.7239 g (0.00535 mol, 1 equivalent) of BTDA was dissolved in 15 mL of DMAc and stirred at 1 mL min. -1 The mixture was added dropwise at a rate of 1.5 wt %. After 1 hour of reaction, the filler (PDA@LM) was added and the reaction was further carried out for 11 hours while maintaining an ice bath to obtain a polyurea-amic acid solution containing liquid metal microcapsules (PDA@LM), wherein the mass of PDA@LM in the polyurea-amic acid solution containing liquid metal microcapsules (PDA@LM) was 1 wt % of the mass of the polyurea-amic acid solution.
[0064] (3) The PEEK / PTFE fiber fabric was repeatedly immersed and dried in a dilute solution of polyurea-amic acid containing liquid metal microcapsules (PDA@LM) until the mass fraction of the PEEK / PTFE fiber fabric in the fabric / resin composite material reached 70-80wt%. Finally, the impregnated PEEK / PTFE self-lubricating fabric was bonded to the surface of the metal part and cured to obtain a PEEK / PTFE self-lubricating fabric composite material. The mass fraction of the PEEK / PTFE fiber fabric in the fabric / resin composite material reached 70-80wt%. Under the test conditions of a rotation speed of 600 r / min and a load of 24.96 MPa, the friction coefficient of the composite material was 0.071 and the wear rate was 6.32×10 -14 m 3 / N·m.
[0065] Example 1
[0066] (1) Add 1g of liquid metal (GaIn) into 100mL of deionized water, and use a high-speed shear dispersion device (shear speed between 8000r / min) to disperse the liquid metal into micro-nano particles (25nm~3μm). After 5min, add 0.5g of dopamine hydrochloride, wait for 25 minutes, and stop shearing and stirring. Add the above solution to 145mL of deionized water and stir to mix the solution evenly. Then drop 5mL of tris buffer solution (PH=8.5) and stir slowly for 48h to induce dopamine polymerization. Finally, collect the PDA@LM gray-black powder by filtration, wash it repeatedly with deionized water five times, and put it in a 40℃ oven to dry for 12h.
[0067] (2) Take 100 mg of PDA@LM powder, add it to 40 mL of deionized water, add 1200 mg of ammonium molybdate tetrahydrate, and 1000 mg of thiourea. After ultrasonication for 1 h, put it into a hydrothermal reactor and react at 220 ° C for 6 h. After the reaction, the black product was repeatedly washed five times with deionized water and dried in a 40 ° C oven for 12 h to obtain MoS2@LM black powder.
[0068] (3) 4.1606 g (0.008025 mol) of HFBAPP and 0.4070 g of DABA were dissolved in 20 mL of DMAc under magnetic stirring. Subsequently, 0.8999 g (0.00535 mol, 1 equivalent) of hexamethylene diisocyanate was slowly added dropwise and stirred continuously for 8 h in a nitrogen atmosphere at 60 °C. Then, 1.7239 g (0.00535 mol) of BTDA was dissolved in 15 mL of DMAc and stirred at 1 mL min. -1The mixture was added dropwise at a rate of 1.5 wt %. After 1 h of reaction, the filler (MoS2@LM) was added and the reaction was further carried out for 11 h while maintaining the ice bath to obtain a polyurea-amic acid solution containing surface-modified liquid metal microcapsules, wherein the mass of MoS2@LM in the polyurea-amic acid solution containing surface-modified liquid metal microcapsules was 1 wt %.
[0069] (4) The PEEK / PTFE fiber fabric is repeatedly immersed and dried in a dilute solution of polyurea-amic acid containing surface-modified liquid metal microcapsules until the mass fraction of the PEEK / PTFE fiber fabric in the fabric / resin composite material reaches 70-80wt%. Finally, the impregnated PEEK / PTFE self-lubricating fabric is bonded to the surface of the metal part and cured to obtain a PEEK / PTFE self-lubricating fabric composite material, and the mass fraction of the PEEK / PTFE fiber fabric in the fabric / resin composite material reaches 70-80wt%. Under the test conditions of a rotation speed of 600r / min and a load of 24.96MPa, the friction coefficient of the composite material is 0.063 and the wear rate is 2.32×10 -14 m 3 / N·m.
[0070] Example 2
[0071] The preparation method is basically the same as that of Example 1, except that the shear rate of the high-speed shear dispersion equipment in step (1) is 20,000 r / min.
[0072] Example 3
[0073] The preparation method is basically the same as that of Example 1, except that the shear rate of the high-speed shear dispersion equipment in step (1) is 1000 r / min.
[0074] Example 4
[0075] The preparation method is basically the same as that of Example 1, except that in step (3), the mass percentage of MoS2@LM to the mass percentage of the polyurea-amic acid solution is preferably 0.01 wt%.
[0076] Example 5
[0077] The preparation method is basically the same as that of Example 1, except that in step (3), the mass percentage of MoS2@LM to the mass percentage of the polyurea-amic acid solution is preferably 6 wt %.
[0078] Example 6
[0079] The preparation method is basically the same as that of Example 1, except that in step (3), the mass percentage of MoS2@LM to the mass percentage of the polyurea-amic acid solution is preferably 3 wt %.
[0080] The tribological properties of the composite materials prepared in Example 1 and Comparative Example 1 and Comparative Example 2 were tested. The test conditions included: 600 r / min, 12.48 MPa, or 600 r / min, 24.96 MPa. The test results are as follows: Figure 1 and Figure 2 As shown, Figure 1 The wear rate of the self-lubricating gasket material prepared in Example 1 of the present invention and Comparative Examples 1-2. Figure 2 The friction coefficient of the self-lubricating gasket material prepared in Example 1 and Comparative Examples 1-2 of the present invention is shown in the analysis of the test results. Compared with the fiber fabric composite material without adding liquid metal microcapsules (Comparative Example 1, PURI-COOH) (test conditions 600r / min, 12.48MPa), when polydopamine-coated liquid metal microcapsules are added (Comparative Example 2, PL), the wear rate of the fiber fabric self-lubricating composite material is increased from 7.54×10 -14 m 3 / N·m is reduced to 4.67×10 -14 m 3 / N·m, after adding MoS2-coated liquid metal microcapsules (Example 1, PM), the material wear rate was further reduced to 4.35×10 -14 m 3 / N·m, compared with the unmodified fiber fabric composite material, the wear rate was reduced by 42.3%. When the test load increased from 12.48MPa to 24.96MPa and the speed was 600r / min, the wear rate of the product PURI-COOH in comparative example 1 was 6.82×10 -14 m 3 / N·m, the PL of the product of comparative example 2 is 6.32×10 -14 m 3 / N·m, the wear rate of PM of Example 1 is 2.32×10 -14 m 3 / N·m, indicating that the wear rate of the molybdenum disulfide coated liquid metal microcapsule reinforced fiber fabric composite material prepared in Example 1 of the present invention is reduced by 65.9% compared with the unmodified composite material. It can be seen from the above embodiments and comparative examples that under different working conditions (test working condition 600r / min, 12.48MPa, or test working condition 600r / min, 24.96MPa), the molybdenum disulfide coated liquid metal microcapsule reinforced composite material prepared in Example 1 shows the smallest friction coefficient.
[0081] The tribological performance test results of the PEEK / PTFE self-lubricating fabric composite materials prepared in Examples 2 to 6 are similar to those in Example 1.
[0082] From the above examples, it can be seen that the present invention uses a mechanical dispersion-interfacial polymerization method to encapsulate liquid metal with excellent lubrication and thermal conductivity in the shell layer of polydopamine and two-dimensional layered materials to prepare microcapsules. At the same time, an in-situ polymerization method is used to connect the microcapsules and the resin matrix through chemical bonds to improve the dispersion stability and uniformity of the microcapsules in the resin, so that the microcapsules are evenly dispersed in the resin matrix, and the above-mentioned resin containing liquid metal microcapsules is used to prepare a fiber fabric self-lubricating composite material, so as to achieve the improvement of the thermal conductivity of the composite material and the improvement of the tribological properties of the composite material under high-speed conditions, and finally achieve the purpose of increasing the service life of the metal parts of the fiber fabric self-lubricating composite material as a lubricating layer.
[0083] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A surface-modified liquid metal microcapsule, characterized in that: It includes liquid metal microcapsules and two-dimensional layered materials in-situ grown on the outer surface of the liquid metal microcapsules; the liquid metal microcapsules include liquid metal and an organic polymer shell layer wrapping the liquid metal, the liquid metal is a micro-nano particle size, and the organic polymer shell layer includes polydopamine or a polydopamine copolymer.
2. The surface-modified liquid metal microcapsule according to claim 1, characterized in that: The liquid metal includes gallium-based liquid metal and / or lithium-based liquid metal; The polydopamine copolymer includes a copolymer of tannic acid and / or polyethyleneimine and dopamine; The two-dimensional layered material includes one or more of molybdenum disulfide, tungsten disulfide and layered MOF materials.
3. The method for preparing the surface-modified liquid metal microcapsules according to claim 1 or 2, characterized in that: The following steps are involved: The liquid metal is sheared and dispersed to obtain a micro-nano-scale liquid metal dispersion; The micro-nanoscale liquid metal dispersion is coated with an organic coating material through a polymerization reaction to obtain liquid metal microcapsules, wherein the organic coating material includes dopamine; The surface of the liquid metal microcapsule is modified by solvent thermal reaction using raw materials for preparing the two-dimensional layered material, and the two-dimensional layered material is in situ grown on the surface of the liquid metal microcapsule to obtain the surface-modified liquid metal microcapsule.
4. The preparation method according to claim 3, characterized in that: The shearing speed of the shear dispersion is 1000-200000 r / min.
5. A resin material, characterized in that: The invention comprises a thermosetting resin solution and a lubricating filler uniformly dispersed in the thermosetting resin solution, wherein the lubricating filler is the surface-modified liquid metal microcapsule according to claim 1 or 2 or the surface-modified liquid metal microcapsule prepared by the preparation method according to claim 3 or 4.
6. The resin material according to claim 5, characterized in that The thermosetting resin solution includes one or more of a polyureaimide resin solution, a polyimide resin solution, an epoxy resin solution, and a phenolic resin solution; The mass of the lubricating material accounts for 0.01-6% of the mass of the thermosetting resin solution.
7. The method for preparing the resin material according to claim 5 or 6, characterized in that: The following steps are involved: The resin material is prepared by an in-situ polymerization method using a thermosetting resin polymerization precursor and a lubricating filler.
8. A liquid metal microcapsule reinforced fiber fabric self-lubricating composite material, characterized in that: The invention comprises a resin matrix and fiber fabrics distributed in the resin matrix, wherein the resin matrix is formed by the resin material according to claim 5 or 6 or the resin material prepared by the preparation method according to claim 7.
9. The liquid metal microcapsule reinforced fiber fabric self-lubricating composite material according to claim 8, characterized in that: The mass of the fiber fabric accounts for 30-85% of the total mass of the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material.
10. The method for preparing the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material according to claim 8 or 9, characterized in that: The following steps are involved: The fiber fabric grey cloth and the resin material are compounded to obtain the liquid metal microcapsule reinforced fiber fabric self-lubricating composite material; the compounding includes repeated impregnation-drying operations.